1992
DOI: 10.1161/01.atv.12.4.494
|View full text |Cite
|
Sign up to set email alerts
|

Collagens in human atherosclerosis. Immunohistochemical analysis using collagen type-specific antibodies.

Abstract: This study represents a systematic analysis of the distribution of collagen types in human atherosclerotic lesions. Formalin-fixed, paraffin-embedded aortic tissues of 40 lesions from 16 different individuals ranging in age from 1 month to 84 years were examined immunohistochemically using antibodies to type I, III, IV, V, and VI collagens. Preembedding immunoelectron microscopy was used to simultaneously localize type V and VI collagens within the lesions. Localization of type HI collagen was very similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
127
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(133 citation statements)
references
References 54 publications
3
127
0
3
Order By: Relevance
“…14,15 In addition, collagen type IV has been shown to be present in the intima of fatty streaks and in advanced lesions. 16 Collagen type IV interaction to endothelial cells is important for maintaining endothelial cell function. 12 Whether collagen type IV directly interacts with LDL and thereby is exposed to reactive aldehydes, or if this exposure is due to an indirect interaction between collagen type IV and other extracellular matrix proteins/proteoglycans binding LDL, remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition, collagen type IV has been shown to be present in the intima of fatty streaks and in advanced lesions. 16 Collagen type IV interaction to endothelial cells is important for maintaining endothelial cell function. 12 Whether collagen type IV directly interacts with LDL and thereby is exposed to reactive aldehydes, or if this exposure is due to an indirect interaction between collagen type IV and other extracellular matrix proteins/proteoglycans binding LDL, remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The newly synthesised collagen that constitutes the major ECM component, [28] marks the aggravation of the cellular alteration due to diabetes and causes fibrosis state. [29,30,31] In fact, the fibrosis of the aortic wall would be due to the presence of collagen, [32] which is dominant in the proliferative intima. [33] Our qualitative and quantitative study on the phenotypic expression of collagen has shown that cultured SMCs of the normal and diabetic Psammomys obesus synthesise more type I than type III collagen, in accord with the results of Layman et al [34] [36] have shown that SMC produced essentially collagen I and III.…”
Section: Discussionmentioning
confidence: 99%
“…[33] have noted equally an increase of mRNA coding for 01 (I) zl (III) chains after 30 days of experimental angioplasty. Katsuda et al [32] have shown the coexistence of the two phenotypes in the intimal lesions, but type I collagen would stimulate the SMC migration, t38] During the development of the atherosclerotic process, many authors showed that collagen molecules are also subject to qualitative alterations.…”
Section: Discussionmentioning
confidence: 99%
“…22 At least 6 collagen types (I, III, IV, V, VI, and VIII) are present in blood vessels, 23 and a predominance of interstitial collagen types I and III has been documented in atherosclerotic lesions, where they appear to be codistributed in different amounts within all 3 layers of the artery wall. 10,24 Notwithstanding the considerable advances made in the area relating to arterial collagens of normal and atherosclerotic tissues, the available information remains incomplete and, above all, inconsistent and controversial. 20,25,26 The initial work on the status of interstitial collagens 3 suggested that there is a shift in favor of type I collagen in fibrous atherosclerotic lesions compared with the normal arterial wall, where type III collagen predominates.…”
Section: Discussionmentioning
confidence: 99%
“…The organic matrix of a plaque consists mainly of collagen types I and III, but controversy exists over their contents and changes in their proportions between the healthy and atherosclerotic aorta. [3][4][5][6][7][8][9][10] A currently unknown proportion of type III collagen still carries the amino-terminal propeptide domain of its precursor, type III procollagen. 11 Regarding atherosclerotic manifestations, we have previously demonstrated increased serum levels of this propeptide, PIIINP, after both streptokinase and tissue plasminogen activator treatments after acute myocardial infarction 12,13 and detected increased serum levels of PIIINP in patients with expanding abdominal aortic aneurysms.…”
mentioning
confidence: 99%